THE SYNTHESIS OF AN UNSYMMETRICAL SALEN-TYPE LIGAND AND ITS COBALT COMPLEX AS AN EFFICIENT CATALYST FOR THE HYDROLYTIC KINETIC RESOLUTION OF EPICHLOROHYDRIN - Nam, Phan T. S.; Christopher, Jones W. (Vietnam Journal of Chemistry, 2012)
An unsymmetrical salen-type ligand, (R,R)-N-(3,5-di-tert-butylsalicylidene)-N’-[3-tert-butyl-5-(4-vinylphenyl)salicylidene]cyclohexane-1,2-diamine, was readily synthesized using the condensation of (R,R)-cyclohexane-1,2-diamine with 3,5-di-tert-butyl-2-hydroxybenzaldehyde and 3-tert-butyl-2-hydroxy-5-(4-vinylphenyl)benzaldehyde in an isolated yield of 80%. The ligand was characterized using 1H and 13C NMR, MS and HRMS, elemental analysis. The corresponding cobalt (II) complex was subsequently prepared and characterized using HRMS and elemental analysis. It was observed that the salen-type cobalt complex exhibited excellent activity and selectivity in the hydrolytic kinetic resolution of racemic mixture of epichlorohydrin, with more than 99% ee and 53% conversion being achieved within 2 h at the catalyst loading of 0.5 mol%.